Optimism and resilience among university students - Rocio Gómez- Molinero; Antonio Zayas; Paula Ruíz-González; Rocio Guil (INFAD, 2018)
University life is full of stressful stimuli that can contribute to psychological distress and lower performance levels. Despite academic demands, university students also face new stressors, such as different social networks, financial changes, and adaptation to new family and social roles that may have a negative impact on their mental health (Pidgeon Pickett, 2017). In this sense, resilience literature has gained acceptance explaining how some students successfully adapt to university life while others find great challenges. Since resilience has been defined as the ability to successfully adapt in the face of stress and adversity, it is important to determine what psychological factors contribute enhancing this resilience levels. One of the factors related to life adaptation is optimism, understood as the general expectancy of obtaining positive outcomes in the future (Scheier Carver, 1985). Hence, the aim of this study is to study the relationship between optimism and resilience among a sample of university students in Spain.